An ammonia power system with zero-carbon potential: A next power? - Jingyu Wang; Ligeng Li; Xuanang Zhang; Yiwei Yin; Hua Tian; Gequn Shu; Zhenyuan Zi; Yu Chen (Next Energy)
As a critical sector for carbon emissions, reducing carbon emissions in transportation internal combustion engines (ICE) remains an important issue. Ammonia has demonstrated strong performance and zero-carbon potential in ICEs and heat utilization. Therefore, this discussion proposes a zero-carbon engine concept to achieve energy savings and emission reductions. The proposed engine is an ammonia medium hybrid engine (AMHE), which utilizes ammonia as the sole working medium to achieve power conversion through combustion and heat exchange within the power system. This discussion demonstrates that the AMHE has the potential to reach the world-advanced level, with a brake thermal efficiency of 59.3%. With the development of blue ammonia to green ammonia, the promotion of the AMHE could reduce CO2 emissions by 64.32–98.90%, equivalent to over 220 million tons in China's transportation sector. Thermodynamic analysis demonstrates that the ammonia diesel cycle achieves the ignition temperature at a compression ratio of approximately 22, which is significantly lower than the previously expected value of 35. This discussion also analyzes the impact of diesel cycle parameters on the Rankine cycle (RC) performance and explores the potential for performance enhancement and compression ratio reduction when using the ammonia RC instead of jacket water. This discussion aims to propose the AMHE as a viable solution for power systems with zero-carbon potential. To this end, we validate its performance and carbon reduction potential of the AMHE and outline future research directions and priorities for this power system.